Improving the stability of black soil microbial communities through long-term application of biochar to optimize the characteristics of DOM components - Yu Hu; Yan Li; Kangmeng Liu; Chuanqi Shi; Wei Wang; Zhenguo Yang; Kuifeng Xu; Shuo Li; Yuxian Wang; Liang Jin; Dan Wei; Lilong Yan (Biochar)
Abstract Biochar has demonstrated to have ability to improve soil properties and boost plant productivity. However, the underlying mechanisms by which dissolved organic matter (DOM) fluorescent components and microbial communities in black soil regions contribute to plant productivity remain uncertain. To address this gap, a long-term field experiment was conducted in Northeastern China’s black soil region, investigating how varying biochar application rates (0, 15.75, 31.50, and 47.25 t ha⁻1) influence DOM fluorescence properties and the composition of soil microbial communities. Employing fluorescence excitation–emission matrix-parallel factor analysis (EEM-PARAFAC) and high-throughput sequencing, the research systematically analyzed how biochar amendments influence DOM composition, fluorescence properties, microbial diversity, and their interrelations. The findings demonstrated that biochar significantly modified DOM composition, increasing the proportions of protein-like and humic substances while enhancing its aromaticity and stability. A medium application rate (31.5 t ha⁻1) notably improved alpha- and beta-diversity within the soil microbial community, optimized a co-occurrence network dominated by Proteobacteria and Acidobacteria, and facilitated key DOM transformations and nutrient cycling. In contrast, a high biochar application rate (47.25 t ha⁻1) negatively impacted the stability of microbial communities. Structural equation modeling (SEM) revealed that biochar indirectly boosted crop yields by modulating DOM fluorescence and microbial community dynamics. The insights gained from this study provide practical guidance for optimizing biochar application rates, maximizing its benefits, and mitigating potential ecological risks in black soil systems. Graphical Abstract